2019
DOI: 10.32718/nvlvet9512
|View full text |Cite
|
Sign up to set email alerts
|

The effects of falsification of meat of slaughtered animals with sodium hydrocarbonate on their quality and safety

Abstract: State monitoring is carried out to verify compliance with the requirements of the legislation on safety and individual indicators of food quality by market operators who produce meat and meat products, store (wholesale bases) and sell (agro-markets, supermarkets, etc.). When establishing a food hazard, the following conditions are taken into account: the usual conditions of use of the food by the consumer, each stage of its production, processing and circulation; information provided to the consumer, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Alsayeqh (2022), the degree of microbial contamination is one of the important indicators of meat safety, especially when storing it in a chilled state. Microscopic analysis of prints of pork samples from both the control and experimental groups on the 4 th day of storage revealed that the number of microorganisms in the field of view did not depend on the method of processing half-carcasses (Table 2) and was within the limits characteristic of Information of N. Bogatko (2019) for chilled meat. Half-carcass washing, in this case, did not affect the microbial contamination of pork, which is consistent with the results obtained by I.F.…”
Section: Resultsmentioning
confidence: 92%
“…Alsayeqh (2022), the degree of microbial contamination is one of the important indicators of meat safety, especially when storing it in a chilled state. Microscopic analysis of prints of pork samples from both the control and experimental groups on the 4 th day of storage revealed that the number of microorganisms in the field of view did not depend on the method of processing half-carcasses (Table 2) and was within the limits characteristic of Information of N. Bogatko (2019) for chilled meat. Half-carcass washing, in this case, did not affect the microbial contamination of pork, which is consistent with the results obtained by I.F.…”
Section: Resultsmentioning
confidence: 92%